Evaluasi Negatif dalam Kosakata Ujaran Kebencian di Twitter Perspektif Analisis Wacana Kritis Norman Fairclough - Suriadi, Suriadi; Baharman, Baharman (Nuances of Indonesian Language, 2025)
This research aims to analyze the motives behind the use of hate speech vocabulary features on Twitter. The research was conducted using a descriptive qualitative method. Data was collected through three stages: carefully reading tweets containing hate speech, documenting the tweets in the form of screenshots, and recording the tweets in a data classification table. Subsequently, the data was analyzed using Norman Fairclough's critical discourse analysis theory, encompassing text analysis, interpretation of discourse context, and explanation of social practice. The data analysis focused on the negative evaluation of hate speech. The results of the data analysis show that the negative evaluation of hate speech takes the form of insults directed at an individual's personality and insults directed at physical appearance (body shaming). These utterances aim to discredit certain parties and denigrate others.